Highly sensitive fiber ring laser sensor for curvature using a modal interferometer (2020)
A curvature sensing Ytterbium-doped fiber ring,using a Thin Core Fiber Modal Interferometer (TCFMI) was experimentally demonstrated in this work. The TCFMI was implemented by fusion splicing a segment of a thin-core fiber, with a small core diameter, between two single-mode fiber sections. The proposed TCFMI functioned as a wavelengthselective filter in the fiber ring laser cavity. It was optimized to achieve a Side Mode Suppression Ratio (SMSR) of 35 dB; the laser emission produced a sensor resolution of 0.37 nm. The experimental results also showed a high curvature sensitivity close to −38.26 nm/m−1 from 0 m−1 to 0.399 m−1 curvature range. Here, the laser sensor exhibited a bandwidth of 16 nm in the 1072 nm to 1056 nm wavelength range. The fiber ring laser is a low-cost alternative for curvature sensing applications